Late‐Life Factors Associated with Healthy Aging in Older Men. Issue 5 (29th April 2014) - Bell, Christina L.; Chen, Randi; Masaki, Kamal; Yee, Priscilla; He, Qimei; Grove, John; Donlon, Timothy; Curb, J. David; Willcox, D. Craig; Poon, Leonard W.; Willcox, Bradley J.
<x xml:space="preserve">Abstract</x> Objectives To identify potentially modifiable late‐life biological, lifestyle, and sociodemographic factors associated with overall and healthy survival to age 85. Design Prospective longitudinal cohort study with 21 years of follow‐up (1991–2012). Setting Hawaii Lifespan Study. Participants American men of Japanese ancestry (mean age 75.7, range 71–82) without baseline major clinical morbidity and functional impairments (N = 1, 292). Measurements Overall survival and healthy survival (free from six major chronic diseases and without physical or cognitive impairment) to age 85. Factors were measured at late‐life baseline examinations (1991–1993). Results Of 1, 292 participants, 1, 000 (77%) survived to 85 (34% healthy) and 309 (24%) to 95 (<1% healthy). Late‐life factors associated with survival and healthy survival included biological (body mass index, ankle–brachial index, cognitive score, blood pressure, inflammatory markers), lifestyle (smoking, alcohol use, physical activity), and sociodemographic factors (education, marital status). Cumulative late‐life baseline risk factor models demonstrated that age‐standardized (at 70) probability of survival to 95 ranged from 27% (no factors) to 7% (≥5 factors); probability of survival to 100 ranged from 4% (no factors) to 0.1% (≥5 factors). Age‐standardized (at 70) probability of healthy survival to 90 ranged from 4% (no factors) to 0.01% (≥5 factors). There were nine healthy survivors at 95 and one healthy survivor at 100. Conclusion Several potentially modifiable risk factors in men in late life (mean age 75.7) were associated with markedly greater probability of subsequent healthy survival and longevity.